A Study of Differences in Enjoyment, Exercise Commitment, and Intention to Continue Participation Among Age Groups of Adult Amateur Golfers - Hye Jin Yang; Ji-Hye Yang; Chulhwan Choi; Chul-Ho Bum (Behavioral Sciences)
Golf is one of the leisure sports that offers various benefits and has become a popular public sport with participation from people of various age groups. A total of 262 questionnaires were distributed online, with 240 valid responses collected after excluding 22 with non-responses or partial answers. The results showed statistically significant differences in enjoyment by age group, except for recognition from others. Regarding physical health, those in their 60s and above had higher mean scores than other age groups, and those in their 50s scored higher than those in their 30s. Stress relief was greater among those in their 50s than among those in their 20s and 30s, while socialization was higher among those in their 50s than in their 20s. However, for skill improvement, participants in their 20s scored higher than those in their 50s and 60s and above. Exercise commitment and intention to continue participation also varied significantly by age group, with older participants generally scoring higher. In conclusion, the results of this study revealed significant differences in psychological factors among the age groups. Specifically, amateur golfers aged 50 and above showed higher mean scores in all variables compared to younger groups.